2011
DOI: 10.1080/02642060902942964
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate reputations on customer perceptions and cross-buying intentions

Abstract: Cross-selling additional services to existing customers is an important task for multiservice companies. This paper examines whether and how a corporate reputation influences customers' economically orientated (that is, perceived benefits of buying new services from current supplier) and relationship perceptions (that is, evaluations of relationship strength and supplier's offerings) and, in turn, their cross-buying intentions. Good corporate reputations build customer cross-buying intentions by increasing cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…Positive wordof-mouth is the likelihood of spreading positive information about an organization [30,31]. Jeng [32] found that corporate reputation and satisfaction raise cross-buying intentions by decreasing information costs and enhancing trust and affective commitment. Similarly, studies by Bolton and Lemon [33] and Mittal and Kamakura [34] show a positive effect of satisfaction on further usage levels and repurchase behavior and cross-purchase preferences.…”
Section: Outcome Intentionsmentioning
confidence: 99%
“…Positive wordof-mouth is the likelihood of spreading positive information about an organization [30,31]. Jeng [32] found that corporate reputation and satisfaction raise cross-buying intentions by decreasing information costs and enhancing trust and affective commitment. Similarly, studies by Bolton and Lemon [33] and Mittal and Kamakura [34] show a positive effect of satisfaction on further usage levels and repurchase behavior and cross-purchase preferences.…”
Section: Outcome Intentionsmentioning
confidence: 99%
“…The resources the franchisor makes available to be used by the franchisee is a determining factor for franchisees to enter into franchising. For instance, in franchising, franchisors provide at least two important resources: brand (Jeng, ; Michael, ) and operational routines (Knott, ). All other opportunities that accrue to a franchisee resulting from the resources, experiences, and services of a franchisor may determine the franchising decision of the franchisee.…”
Section: Motivations For Franchisingmentioning
confidence: 99%
“…Good corporate reputations establish customer cross-buying intentions by enhancing expected service quality of customers, reducing information costs, and increasing trust and affective commitment [11,12]. In modern times, companies have to comprehend the actual standing of their products on the Web in that more and more consumers depend on online opinions when making purchasing decisions [14].…”
Section: Introductionmentioning
confidence: 99%